2002
DOI: 10.1210/jcem.87.6.8673
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism in the IGF-I Gene: Clinical Relevance for Short Children Born Small for Gestational Age (SGA)

Abstract: Low birth weight is associated with an increased risk in adult life of type 2 diabetes, hypertension and cardiovascular disease (CVD). The fetal insulin hypothesis postulates that genes involving insulin resistance could effect birth weight and disease in later life (Hattersley, 1999). Besides insulin, there is extensive evidence that insulin-like growth factor-I and -II (IGF-I, IGF-II) play an important role in fetal growth. We hypothesized that minor genetic variation in the IGF-I gene could influence pre- a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
50
1
5

Year Published

2002
2002
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(62 citation statements)
references
References 0 publications
6
50
1
5
Order By: Relevance
“…Abramovitcha et al (2003) have presented evidence suggesting a link between the IGF-1 system and BRCA1, and reported that the transcription of the IGF-1 receptor gene in breast cancer-derived cell lines is under the inhibitory control of BRCA1. Others have reported that the IGF1 genotype is linked to a low birth weight (Arends et al, 2002) and we have previously reported low birth weight among BRCA1 carriers compared with non-carriers from BRCA1 families (Jernström et al, 1998), although no IGF-1 genotyping was performed in the latter study. The link between the IGF-1 system and the BRCA1 gene clearly warrants further study, and we are currently undertaking IGF1 genotyping of all BRCA1 carriers to elucidate whether the absence of the 19-repeat allele is more frequent in mutation carriers than non-carriers.…”
Section: Discussionmentioning
confidence: 64%
“…Abramovitcha et al (2003) have presented evidence suggesting a link between the IGF-1 system and BRCA1, and reported that the transcription of the IGF-1 receptor gene in breast cancer-derived cell lines is under the inhibitory control of BRCA1. Others have reported that the IGF1 genotype is linked to a low birth weight (Arends et al, 2002) and we have previously reported low birth weight among BRCA1 carriers compared with non-carriers from BRCA1 families (Jernström et al, 1998), although no IGF-1 genotyping was performed in the latter study. The link between the IGF-1 system and the BRCA1 gene clearly warrants further study, and we are currently undertaking IGF1 genotyping of all BRCA1 carriers to elucidate whether the absence of the 19-repeat allele is more frequent in mutation carriers than non-carriers.…”
Section: Discussionmentioning
confidence: 64%
“…In contrast, an IGF-I gene deletion or mutation results in severe intrauterine growth retardation as is demonstrated in the patient described by Woods et (K4 and K6.5 SDS respectively) (13)(14)(15). The finding that genetically determined low IGF-I levels, due to polymorphisms in the IGF-I promoter region, result in a reduced birth weight and length support the role of IGF-I in fetal growth (16,17).…”
Section: Intrauterine Growthmentioning
confidence: 80%
“…In humans, genetic defects of IGF‐1 and IGF‐1 receptor are rarely seen in viable infants, but four case reports of polymorphisms of the IGF‐1 gene in patients have described intrauterine growth restriction or being born small for gestational age as well as microcephaly, sensorineural deficits, developmental delay and metabolic abnormalities 34, 35. The severity of the foetal growth restriction is illustrated with birth weight standard deviation scores (SDS) ranging from −2.5 to −3.5 (Table 1) 36, 37, 38, 39, 40.…”
Section: Organ‐specific Roles Of Igf‐1 In the Foetusmentioning
confidence: 99%